If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + 5d + -12c = 0 Reorder the terms: c + -12c + 5d = 0 Combine like terms: c + -12c = -11c -11c + 5d = 0 Solving -11c + 5d = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-5d' to each side of the equation. -11c + 5d + -5d = 0 + -5d Combine like terms: 5d + -5d = 0 -11c + 0 = 0 + -5d -11c = 0 + -5d Remove the zero: -11c = -5d Divide each side by '-11'. c = 0.4545454545d Simplifying c = 0.4545454545d
| 2(lnx+1)=0 | | 0.10x+0.05(2-x)=0.10(5) | | 0.10x+0.05(2-x)=0 | | k^2-20k+64=0 | | 27x^6-27x^5+45x^3/-9x^3 | | 16-5(3t-4)=88(-2t+11) | | -8y=-33 | | 8y=-33 | | 5/12k=1/15-3/14 | | 85x-16=0 | | 6x-1=2x+1 | | cos(3x)-sin(2x)=0 | | 22-x=5+6x+9 | | 0=x^2-10x+28 | | 13y=1/15-3/14 | | -9x^2+4x-16=0 | | 3n^3+9n^2-84n=0 | | 4.90=0.05x+1.90 | | 3x-6=25x+18 | | 4(w-2)=0.6 | | 88-40=13/4(h-5) | | (2x-6)+(x+7)= | | 25-n^2=0 | | 23x-5=0 | | 12x-4x^2-9=0 | | 12q^2-17q+5=0 | | 6(x+2)=2(x+10) | | 25b+11-6b^2=0 | | 8x/6=72/54 | | 0.1q-0.2(3q+4)=-0.3(5q+3) | | 3x^3-10x^2-23x-10=0 | | k^2-2k+1=0 |